Killing Politics: The Art of Recovery in Falling Man - Cvek, Sven (2009)
This article analyzes the representation of the aftermath of the Septemeber 11, 2001 attacks in Don DeLillo’s novel Falling Man. By exploring both trauma’s social effects and its metaphorical meanings, DeLillo’s novel registers and enacts the disappearance of politically informed social practice as a communal force in the contemporary US. This disappearance the novel posits as being accomplished through a process of traumatization of the national polity contingent both on a "global" clash of disparate worlds and on domestic interventions of the state. The article proposes that such depoliticization rests on particular constructions of the human citizen and the non- human terrorist, and that it represents a tactic through which the sovereign power of the state is ultimately manifested. DeLillo responds to the state’s instrumentalization of trauma by asserting the possibility of a socially productive aesthetic practice.
Projekt MZOS
ENG